Pemanfaatan Sistem Informasi Manajeman di Pondok Pesantren Modern - Darmawan, Ilyas; Hidayati, Dian (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
In the present time, the development of the education world demands a more multidynamic approach. This means that education requires comprehensive and holistic development. Over time, the development of culture and civilization in the world has brought about changes in all aspects, including social structure, culture, and the education system in Islamic boarding schools (pesantren). Therefore, in the development of education in pesantren, technological management is needed to align with the current era. This research aims to explore the activities of the information system in a pesantren. Data was obtained through interviews, website documentation, and literature review. The data analysis technique adopted the theory of Miles & Huberman (data reduction, data display, data verification, and conclusion drawing). The results of the research are as follows: 1) The implementation of media team activities as an information system platform; 2) The pesantren information system is based on a website and application. This application consists of teacher attendance and teaching notes. The website and social media used by the pesantren include the pesantren portal website, YouTube, Twitter, Facebook, and Instagram as promotional media to the public. The conclusion of this research is that the implementation of the activities runs well.